Novel Granulectomy Technique and Intralesional Triamcinolone for Liquid Injectable Silicone-Induced Chin Granulomas: A Long-Term Ambidirectional Cohort Study - Ago Harlim; Hubert Andrew; Chastine Harlim (Journal of Clinical Medicine, 2026)
Background: Liquid injectable silicone (LIS) is controversially used for soft-tissue augmentation, frequently causing severe, late-onset foreign body granulomas. Complete surgical removal is nearly impossible due to silicone migration, with residues leading to high recurrence. Meanwhile, medical therapies alone do not address macroscopic structural deformity. This study evaluates a combined protocol of subdermal granulectomy followed by adjuvant intralesional steroids for chin siliconomas. Methods: An ambidirectional cohort study (2015–2025) evaluated 35 patients with LIS-induced chin granulomas. All subjects underwent submental granulectomy. Postoperatively, patients were allocated to an adjuvant steroid cohort (n = 17) or a surgery-only control cohort (n = 18). The outcomes included aesthetic improvements (chin shape and erythema) and recurrence-free survival. Results: Granulectomy yielded significant improvements in aesthetics (p = 0.001) and erythema (p < 0.001) with a 2.86% complication rate. Longitudinal survival analysis demonstrated that adjuvant steroids lowered the crude recurrence rate (5.89% vs. 44.4%, p = 0.018) and significantly extended recurrence-free survival (Log-rank p = 0.016). The surgery-only cohort exhibited higher recurrence risk (Cox hazard ratio = 8.59, p = 0.043). Over the follow-up period, the surgery-only cohort experienced significant aesthetic deterioration (p = 0.04) and persistent redness, whereas the steroid cohort preserved postsurgical chin shape (p = 0.19) and achieved further erythema reduction (p = 0.03). Multivariable regression indicated higher odds of aesthetic preservation (adjusted odds ratio [aOR] = 3.85, p = 0.082) and erythema resolution (aOR = 2.90, p = 0.145) in the steroid cohort, although statistical significance was not reached. Conclusions: Our subdermal granulectomy technique successfully removed macroscopic silicone burden while maintaining the appearance of the anterior chin. The implementation of an early adjuvant steroid protocol provides a synergistic advantage by neutralizing residual microscopic inflammation, delaying recurrence, and ensuring durable aesthetic outcomes.